Carcinogenic Effects of Lead (Pb) on Public Health - Chatha, Ahmad Manan Mustafa; Naz, Saima; Abbas, Zaigham; Rehman, Shafiq Ur (BioScientific Review, 2023)
Lead (Pb) is a potentially hazardous metal that penetrates the bones and blood as well as other major organs including the skin, liver, kidneys, and brain after being absorbed by the body. It is the most abundant heavy metal found in nature and utilized for a variety of industrial purposes. Lead is used in the manufacturing of bearings and printing fonts, as well as in the manufacturing of sulfuric acid, cable coverings, soldering products, guards in nuclear power stations, shields, vessels for radiation emitting materials, paints, ceramics, chemicals, and building structures. It is advantageous for physiological and biochemical processes in living beings in low concentrations. However, when it surpasses a specific threshold, it causes significant health issues. Lead is extremely persistent in nature and its continued use causes serious toxicological impacts, such as renal failure, carcinogenicity, high blood pressure, hematological effects, brain damage, reproductive system complications (in both men and women), bone screening, heart diseases, and liver damage. The available treatments, such as chelation therapy and other types of medicines, can help to reduce its adverse effects. The objective of this review is to delineate the adverse effects of lead on the human body, spanning from childhood to adulthood. Lead is a cumulative toxicant that affects multiple body systems and is particularly harmful to young children. The second major goal of this study is to define lead contamination and identify its sources and levels.